Twice shy - Hogle, Sarah (G.P. Putnam's Sons, 2021)
"Maybell Parrish living with her head in the clouds has always felt preferable to dealing with reality ... So when Maybell inherits a stately old Tennessee manor from her eccentric Great Aunt Violet, she realizes it's the perfect opportunity ... But when she arrives at her new home, the manor is practically falling apart around her, but its handsome yet reclusive groundskeeper, Wesley Koehler ... seems to want nothing to do with her ... But when Maybell discovers that beneath his brooding exterior lies an anxiety that exceeds her own, she realizes they might have more in common than she ever dreamed" --